Inclusion under the Mental Capacity Act (2005): A review of research policy guidance and governance structures in England and Wales. (27th November 2020) - Ryan, Hayley; Heywood, Rob; Jimoh, Oluseyi; Killett, Anne; Langdon, Peter E; Shiggins, Ciara; Bunning, Karen
Abstract: Objective: To investigate how people with communication and understanding difficulties, associated with conditions such as dementia, autism and intellectual disability, are represented in research guidance supplementary to the Mental Capacity Act (MCA: 2005) in England and Wales. Methods: A documentary survey was conducted. The sample comprised the MCA Code of Practice (CoP: 2007) and 14 multi‐authored advisory documents that were publicly available on the Health Research Authority website. Textual review of key words was conducted followed by summative content analysis. Results: Representation of people with communication and understanding difficulties was confined to procedural information and position statements that focused mainly on risk management and protection. Whilst a need to engage potential participants was recognized, guidance provided was imprecise. Conclusions: Tensions exist between the protection versus empowerment of people with communication and understanding difficulties in research. The development of structured, evidence‐based guidance is indicated. Patient or public contribution: People with communication and understanding difficulties and carers participated in a working group to explore, discuss and interpret the findings.